Manejo reprodutivo e assistência veterinária a campo em fazendas da região nordeste do Pará - Martin Junior, Carlos Cesar (Universidade Federal do Tocantins, 2023)
This Report consists of the activities developed during the mandatory supervised curricular internship of the Veterinary Medicine course at the Federal University of Tocantins, carried out in the period between 03/07/2022 to 05/16/2022, totaling 390 hours. Under the guidance of Professor Dr. Fabiana Cordeiro Rosa and supervision of the Veterinarian Diego Augusto Rocha. The activities focused on specialized assistance in the area of bovine reproduction in the northeast region of the state of Pará, mainly in the municipalities of Paragominas, Ipixuna, Ulianópolis, Dom Eliseu, Thailand, Tomé Açu, among others, in several rural properties where beef cattle is the main activity. The services provided were: Gestational Diagnosis, Gynecological Assessment of beef heifers, Andrological Examination and monitoring of Assessments for the issuance of the Special Certificate of Identification and Production - CEIP, in addition, we will talk about the importance of genetic improvement programs combined with certificates for maximizing animal production in beef cattle.